Recent overview of mammary cancer in dogs and cats: classification, risk factors and future perspectives for treatment - Nordin, Muhammad Luqman; Osman, Abdinasir Yusuf; Shaari, Rumaizi; Arshad, Mohd Mokhtar; Abdul Kadir, Arifah; Reduan, Mohd Farhan Hanif (2017)
Mammary cancer remains as the common cancer in intact female dogs and cats. Its share similarities with human breast cancer as the cancer initially arise from the mammary gland. Therefore, the treatment protocols for the mammary cancer in animal mostly were extrapolated from human breast cancer treatment. In this review, we highlight various key aspects of mammary cancer information in dogs and cats with special emphasis on classification, epidemiology, diagnosis, prognosis, and treatment options. This review also highlights the recommendation for future study as information given could be extrapolated to human breast cancer.